2020
DOI: 10.31893/jabb.20034
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress impact on blood biochemical response and plasma aldosterone level in three different indigenous goat breeds

Abstract: A study was conducted to compare the adaptive ability of three indigenous goat breeds (Osmanabadi, Malabari, and Salem Black) to heat stress. The primary objective of the study was to assess the thermo-tolerant ability of these breeds to heat stress based on the changes in their blood biochemical response and aldosterone concentration. Thirty six-ten months to one year old female goats were randomly allocated into six groups of six animals each as OCON (n=6; Osmanabadi control), OHS (n=6; Osmanabadi heat stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Heat-stress-related dehydration reduced aldosterone concentration in Malabari goats but not in Osmanabadi and Salem Black goats. It has been suggested that Osmanabadi and Salem goats have excellent capability to adapt to harsh conditions [ 15 ]. In Bedouin goats that have extreme resilience to severe water deprivation, aldosterone concentration along with rennin activity increased during dehydration conditions [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heat-stress-related dehydration reduced aldosterone concentration in Malabari goats but not in Osmanabadi and Salem Black goats. It has been suggested that Osmanabadi and Salem goats have excellent capability to adapt to harsh conditions [ 15 ]. In Bedouin goats that have extreme resilience to severe water deprivation, aldosterone concentration along with rennin activity increased during dehydration conditions [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water restriction elicits changes in a number of physiological and behavioral characteristics in animals [ 3 , 5 ]. Water deprivation beyond normal physiological limits first alters hormonal dynamics, such as the renin–angiotensin–aldosterone system, by increasing aldosterone and vasopressin concentrations to reabsorb water and electrolytes for the maintenance of osmotic balance in plasma and intracellular spaces [ 15 , 16 , 17 ]. These responses prevent cell damage, decrease thyroid hormone secretion to reduce energy metabolism and respiratory water loss in thermoneutral conditions, and increase cortisol concentrations to regulate protein, fat, and glucose metabolism [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, due to the availability of water ad libitum, the response of the renin-angiotensin system is not accompanied by a high plasma concentration of aldosterone. Indeed, Aleena et al (2020) reported that under heat stress, the level of plasma aldosterone was significantly lower in Malabari goats, which had ad libitum access to water. However, in our study, the highest aldosterone concentration coincides with the autumn and spring equinoxes and not with periods of high temperature.…”
Section: Aldosteronementioning
confidence: 99%